Adverse Impacts of Oil Spills on Marine, Lowland and Upland Ecosystems of Niger Delta of Nigeria and the Control Measures - Akpan, Etuk Etiese (Advances in Social Sciences Research Journal, 2023)
An oil spill is the accidental or deliberate release of oil into the environment whether terrestrial or marine. Oil spill pollution is a growing environmental concern that harms both terrestrial and aquatic ecosystems. The Niger Delta Region of Nigeria is a plausible victim of these frequent oil spillages caused by equipment failures, corrosion, human errors, willful damages of pipelines and installations and accident etc. The released oil impacts the soil fertility of the region, the surface water, ground water aquifer and the entire marine habitats leading to health challenges, diseases and death, unemployment, and poverty in the region. Pollution sometimes traverses through the food chain to the human consumers. Possible remedial actions include prevention of oil spills, prompt intervention when they occur by containment, recovery and clean up of the spills. Environmental restoration may be required to resuscitate the soil fertility to continue to support agricultural efforts of the local communities in the region.